2013
DOI: 10.1007/s00392-013-0568-z
|View full text |Cite
|
Sign up to set email alerts
|

Persistent angina: highly prevalent and associated with long-term anxiety, depression, low physical functioning, and quality of life in stable angina pectoris

Abstract: The study indicates higher prevalence of persistent angina in patients with diffuse non-obstructive CAD or normal coronary arteries than in patients with obstructive CAD. Persistent angina symptoms were associated with long-term anxiety, depression, impaired physical functioning, and QOL irrespective of the degree of CAD. Contrary to common perception, excluding obstructive CAD in stable angina does not ensure a favorable disease course, and further risk stratification and treatment strategies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
71
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 24 publications
5
71
0
3
Order By: Relevance
“…20 Another study found that participants with nonobstructive atherosclerosis at CAG have more persistent angina compared with participants with obstructive CAD evaluated by using the Seattle Angina Questionnaire. 3 Together, the findings indicate an overall limited association between symptoms and angiographic CAD severity. We further found that degree of CFVR impairment was not associated with symptom characteristics and that the classic characterization of chest pain could not be used to identify CMD.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…20 Another study found that participants with nonobstructive atherosclerosis at CAG have more persistent angina compared with participants with obstructive CAD evaluated by using the Seattle Angina Questionnaire. 3 Together, the findings indicate an overall limited association between symptoms and angiographic CAD severity. We further found that degree of CFVR impairment was not associated with symptom characteristics and that the classic characterization of chest pain could not be used to identify CMD.…”
Section: Discussionmentioning
confidence: 90%
“…1 While previously considered a benign condition, recent studies have found the condition to be associated with persistent chest pain, repeated angiograms, reduced quality of life, and increased cardiovascular morbidity and mortality. [1][2][3] A possible explanation for the discrepancy between symptoms and CAG findings could be ischemia caused by coronary microvascular dysfunction (CMD). Recent studies have convincingly demonstrated that CMD is a strong predictor of cardiovascular prognosis, [4][5][6] and CMD is common in both men and women with no obstructive CAD.…”
mentioning
confidence: 99%
“…Perhaps greater AP severity, as found in DM patients with worse glycemic control, could be hypothesized as part of the explanation. Severity of persistent angina has been shown to be previously associated with impaired physical functioning as well as depression and anxiety, 8 and frequency of angina attacks with emotional, physical, social, and global scores of quality of life. 9 In our analysis, women report more angina compared with men, both overall and in those with comorbid DM.…”
Section: Discussionmentioning
confidence: 99%
“…Približno dve tretjini žensk in ena tretjina moških, ki so prvič na koronarografiji zaradi angine pektoris, imajo korononarne arterije brez ali skorajda brez sprememb. Kljub normalnemu koronarogramu pa je tveganje za pomembne kardiovaskularne dogodke povišano (14). Dolgotrajna in vztrajajoča angina pektoris po koronarografiji je povezana s kar 3-krat višjo prevalenco depresije in 2-krat višjo prevalenco anksioznosti.…”
Section: Anksioznost In Prsna Bolečinaunclassified
“…Zato se poslabša kakovost ži-vljenja in zmanjša telesna zmogljivost pri bolnikih, ki so preboleli miokardni infarkt ali imajo stabilno koronarno bolezen (15)(16)(17). Ena od hipotez o nastanku angine pektoris v vsakdanjem življenju je koronarna mikrovaskularna disfunkcija, na katero naj bi vplivali različni psihosocialni in nevrobiološki mehanizmi, med drugim tudi subjektivno doživlja-nje stresa in fiziološke spremembe v nevroendokrinem in žilnem okolju (14,17).…”
Section: Anksioznost In Prsna Bolečinaunclassified